Vendor-Integrated Learning Model in ICT Education - Sulong, Muhammad Suhaizan; Abdul-Aziz, Azlianor; Sahib, Shahrin (Centre for Teaching and Learning, UTeM, 2008)
Higher learning institutions around the world are aware that ICT is one of the most constantly changing industries. Learning in this field promises an exciting future by keeping up with technology in which constantly learning new things and developing new skills in various specialisations. Each specialisation is designed for a wide range of job opportunities in the fields of Information Technology, Multimedia and Communication. In view of that, we construct a Vendor-Integrated Learning Model (VILM) in efforts to bridge the knowledge gap between technology and skill sets in today’s competitive job markets. VILM emphasis is on the educational process, which put into practice in Universiti Teknikal Malaysia Melaka (UTeM) especially in Faculty of Information and Communication Technology (FTMK). There are three major learning elements namely Information and Communication Technology (ICT) Specialisation, Teaching and Learning Approach and Vendor-Based Certification that aims to provide our students with the knowledge, skills and attitude required to contribute towards and play major roles in a knowledge-based economy. The aim of constructing the model is to integrate the three learning elements to produce highly competent graduates.